Is there a correlation between the increase in cases of willful bodily injury and hospital admissions for falls? An analysis between 2016 and 2020, in the state of São Paulo, highlighting the period of COVID-19 (Research, Society and Development, 2022)
Objective: To investigate the correlation between the growth in the number of cases of willful bodily injury and hospitalizations for falls, with an emphasis on the first year of the COVID-19 pandemic (2020). Methodology: Observational ecological study. For a partial economic assessment of the cost of the disease, sociodemographic data were extracted from Datasus. Then, data on willful bodily injury were extracted from the SSP/SP database. Results: The averages found were 1.39/1.000 inhabitants for mortality rate, 3.7 days for hospital stay and R$ 1.005.91 for the cost per user. The average amount spent, the mortality rate, ethnicities and age groups were statistically significantly different. For women, there was no statistical significance between 2016 and 2020, in the comparison between falls and willful bodily harm. Conclusion: The COVID-19 pandemic required greater attention to the process of reporting victims of violence, due to the difficulty imposed by social isolation.